Multi-stakeholders’ Perspective on water Security in Nallur D.S.Division : A Study though Participatory Action Research - Srikanthan, S.; Jeevasuthan, S. (University of Jaffna, 2020)
Water is vital for life and availability is the prominent indicator for human and social development. This proposed study on water security develops an existing research phenomenon as water remains at the nexus of various global issues including health, hunger, domestic violence and economic growth of nations. This is an attempt to precise the different views, issues and management strategies on water of multi-stakeholders though the approach of participatory action research. The issues like as water shortage, over usage, over extraction, declining quality in drinking water have formed a gossamer that links every aspect of our human life as well as made risk social environment in Jaffna. The government, civil society, businesses and householders have been exercising various pragmatic strategies used to overcome the issues on water over the year. However, the problems related to water seems to be increasing. In this milieu, this preliminary investigation is carried out to consolidate the perspectives that are scattering in diverse groups representing the nallur divisional secretariat. The data was through conducting world café with various stakeholders of nallur division at different levels. The result of this study focuses on the following: the interface between water and people is multifaceted sensation; issues related to water interconnected to their all aspects of life that means not only health but also economic, social political and culture; public awareness on managing their water and common policy on water management for northern province enacted at local govern as well as central government level must be forwarded to sustainable social development of the region.
Keywords: water security; participatory action research; water related issues; multi-stakeholders’ perspective